Prevalence and Susceptibility of Trichomoniasis among Pregnant Women Attending Selected Primary Health Care Centers within Chikun Local Government Area, Kaduna State - Idris, Zubairu; Musa, F. M.; Nmadu, A. G. (Sahel Journal of Life Sciences FUDMA, 2025)
Trichomoniasis is a disease caused by a protozoan parasite called Trichomonas vaginalis which is transmitted through sexual contact. Complications of T. vaginalis include cystitis, cervicitis, urethritis, infertility, low birth weight, neonatal morbidity, and mortality. This study, therefore, was carried out to determine the occurrence of Trichomoniasis among pregnant women attending ante-natal care services in some Primary Health Care Centers (PHC) within the Chikun Local Government Area of Kaduna State. A sample size of 360 was used in the study. High vaginal swab (HVS) samples were collected from each pregnant woman using the septic method. Wet mount preparation and culture method were used to identify T. vaginalis isolates, and the isolates were further confirmed using molecular techniques and a phylogenetic tree. The susceptibility pattern of the drug metronidazole against the isolates was determined using a standard method. The results obtained in this study revealed that 24 (6.7%) samples were positive for T. vaginalis in both wet mount and culture methods. A single 312bp product of the region was amplified in all 24 samples. Partial nucleotide sequences of T. vaginalis isolates using BLAST analysis with reference sequences in the GenBank database showed that twenty-four isolates belonged to T. vaginalis. All isolates were susceptible to the varied Minimum Inhibitory Concentration (MIC) after 24 hours of treatment with metronidazole (0.4, 0.8, 1.6, and 3.2 µg/ml) except the isolates treated with 0.1 µg/ml of metronidazole.